Development of Didactical Design Concepts of Areas of Squares and Rectangles Assisted by Geogebra in Middle School - Rostina Rostina; Sugiatno Sugiatno; Nurfadilah Siregar (STAI Hubbulwathan Duri, 2023)
The comprehension of overarching principles in texts for elementary and junior high school is deficient. The objective of this study is to create an instructional plan for understanding the notion of square and rectangular regions using GeoGebra as a tool. This study employs a didactical design research methodology with a descriptive-qualitative approach. The didactic design discussed in this study pertains to the acquisition of knowledge regarding square and rectangular regions in junior high school. The study was carried out in a public junior high school located in Sungai Raya Kubu Raya. The data sources consist of primary and secondary data. Primary data is collected firsthand from sources in the field, directly from the research subject. The data is derived from test results and observations of eighth-grade students and mathematics teachers, which serve as the foundation for the development of didactical design. The secondary data consists of a literature review, which is derived from relevant literature sources that provide support or relevance to this publication, such as earlier research. The findings revealed that students had difficulties mostly in identifying flat shapes, calculating the area of squares and rectangles, understanding the correlation between square and rectangular areas, and utilising the notion of square and rectangular areas to solve problems. This learning impediment is surmounted by implementing a didactic design. The resulting didactic design incorporates the utilisation of GeoGebra software to address and overcome students' learning hurdles in the context of square and rectangular materials, with a focus on problem-solving.